Time as an outcome measure in fertility-related clinical studies: long-awaited. Issue 8 (9th July 2020) - Sunkara, Sesh K; Zheng, Wenjing; D'Hooghe, Thomas; Longobardi, Salvatore; Boivin, Jacky
Abstract: Time taken to achieve a live birth is an important consideration that is central to managing patient expectations during infertility treatment. However, time-related endpoints are not reported as standard in the majority of fertility-related clinical studies and there is no internationally recognized consensus definition for such endpoints. There is, therefore, a need for meaningful discussions around the selection of appropriate time-related treatment outcome measures for studies evaluating fertility treatments that will be relevant to diverse stakeholders (e.g. patients, healthcare professionals, clinical scientists, authorities and industry). Here, we provide a proposal for the evaluation of time-related outcome measures in fertility-related clinical studies, alongside associated definitions.